Oral Health Care and Aspiration Pneumonia - Salma, Yasmin Hanifa; Murad, Chrysanti; Megantara, Imam (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Oral health care is important to prevent aspiration pneumonia. Poor oral hygiene in elderly patients heightens the risk of aspiration pneumonia due to the growth of potential periodontopathogen bacteria. This literature review aims to describe the effect of oral health care on the incidence of pneumonia and/or the number of oral bacteria.Method: The literature search was conducted based on the PRISMA guideline with the PICO framework by utilizing electronic search engines in databases: PubMed, Cochrane's Library, and Google Scholar from March through May 2024. All articles to be reviewed were ‘’full text” published from 2014 to 2024. An eligibility assessment was conducted based on inclusion and exclusion criteria; thus, seven articles were selected.Result: Mechanical tooth and mouth cleaning, in addition to using mouthwash and moisturizing agents, effectively reduces the risk of aspiration pneumonia in the elderly.Conclusion: Oral health care with mechanical and pharmacological interventions are deemed appropriate to be given to elderly individuals to prevent aspiration pneumonia.